Scattering correcting wavefront shaping for three-photon microscopy - Rauer, Bernhard; de Aguiar, Hilton B; Bourdieu, Laurent; Gigan, Sylvain (Optics letters, 2022)
Three-photon (3P) microscopy is getting traction due to its superior performance in deep tissues. Yet, aberrations and light scattering still pose one of the main limitations in the attainable depth ranges for high-resolution imaging. Here, we show scattering correcting wavefront shaping with a simple continuous optimization algorithm, guided by the integrated 3P fluorescence signal. We demonstrate focusing and imaging behind scattering layers and investigate convergence trajectories for different sample geometries and feedback non-linearities. Furthermore, we show imaging through a mouse skull and demonstrate a novel, to the best of our knowledge, fast phase estimation scheme that substantially increases the speed at which the optimal correction can be found.